Enteral Feeding in Neonatal Hypoxic-Ischemic Encephalopathy - Martinovski, Helen; Khanal, Luna; Kraft, Debra; Natarajan, Girija (American Journal of Perinatology, 2025)
This study aimed to describe feeding outcomes in neonates with hypoxic-ischemic encephalopathy (HIE) and compare characteristics and outcomes in groups discharged home on oral, total/partial nasogastric, and gastrostomy tube feedings.This was a retrospective, single-center cohort study of infants diagnosed with moderate or severe HIE using standard criteria who underwent cooling from January 2017 to June 2022. Data were abstracted from hospital course as well as until 6 months follow-up. Statistical analysis included chi-square test and ANOVA with post hoc Bonferroni correction for between-group comparisons.Among 123 included infants, 95 (77%) fed orally, 11 (9%) required total/partial nasogastric feeds and 17 (14%) had gastrostomy tubes at discharge. A significantly greater proportion of infants with gastrostomy-tube feeds at discharge had intrapartum complications, Apgar scores <5 at 5 and 10 minutes, severe rather than moderate HIE, and seizures. They also had a longer hospital stay, prolonged respiratory support and intubated days, and delayed initiation of feeding. Infants discharged on nasogastric feeds all attained oral feeds at a median (IQR) duration of 54 (6–178) days follow-up. Among the 106 (86%) infants with follow-up data, the gastrostomy group had significantly lower median weight and head circumference centiles compared to the others. Criteria for gavage eligibility were met before discharge in 98 (80%) of the cohort; 42% stayed beyond this benchmark.Earlier identification of eventual gastrostomy tube insertion as well as discharge home on nasogastric feedings may reduce duration of hospitalization in infants with HIE. Our data may provide insights to guide practice improvement for enteral feedings in this population.
Keywords: hypoxic-ischemic encephalopathy; enteral; feeding; gastrostomy; nasogastric